Optimization of Wireless Internet Pricing Scheme in Serving Multi QoS Network Using Various Attributes - Irmeilyana Irmeilyana; Fitri Maya Puspita; Iffah Husniah (Universitas Ahmad Dahlan, 2016)
Pricing scheme in wireless networks were developed to provide maximum benefit to the internet service provider (ISP), where the given scheme can guarantee customer satisfaction and service providers who use such services. So that the proposed model should be able to attract consumer interest in applying such services. In this research we established wireless pricing model that involve QoS attributes then the model will be transformed into a model of optimization. Pricing models in wireless networks will be studied by looking at existing models as a nonlinear programming problem that can be solved optimally using LINGO 11.0. The solution is to maximize the total price for the connection based on the QoS parameters. Optimal results in the maximizing of pricing scheme is achieved when providers set the increase of price changes due to QoS changes and number of QoS value.